The Paradoxical Impact of Globalisation on Womenâ€™s Political Representation: A Review of Situations In Southeast Asia - AZIZAH, NUR (Universitas Muhammadiyah Yogyakarta, 2015)
The representation of women in a political system isÂ a good test of its claims to democracy. AlthoughÂ there are some progress, the level of women political representation in Southeast Asian countries isÂ still low. Women activists propose the adoption ofÂ gender quotas as a fast track to address this issue,Â but the implementation find many obstacles. ThisÂ article base of my research which want to examineÂ the impact of globalisation for womenâ€™s political representation in Southeast Asian countries. The discussion begin with the overview of womenâ€™s politicalÂ representation issue and some theoretical framewoksÂ for adressing that issue. It identified that globalisationÂ has positive and negative impacts on womenâ€™s representation. On the one hand, it encourages theÂ emergence of a global gender equality regime whichÂ influences pattern of womenâ€™s political representation among Southeast Asian countries. Yet, on theotherhand, itpromotes neo-liberalism ideology whichÂ is â€œinherently oppose to policy interventionismâ€andÂ it also promotes liberal democratic practices, whichÂ oppose affirmative policy for women, included gender quota in parliament.We concludes that the paradoxical impact of globalisation causes progress forÂ increasing womenâ€™s representation in Southeast AsianÂ countries move slowly. The efforts for increasingÂ womenâ€™s representation in some Southeast AsianÂ countries have not been supported by governmentsâ€™Â â€œinterventionâ€ policies such as gender quota andÂ social welfare policies. Southeast Asian countries areÂ also trapped in a liberal democracy practice whichÂ promotes â€˜one person one voteâ€™ (equality of opportunity). Thus, the opposition to affirmative action (equality of result) is so high. Although some Southeast Asian countries have women quota articles, the implementation has been undermined so far.KEYWORDS: Globalisation Impact, Women, Political Representation,Southeast Asia